Chronobiology And Circadian Rhythm-Based Daily Regimen In Ayurveda - A Comparative Analysis - Kumar, Sadhna; Nachankar, Siddhi Ratnakar; Kuchewar, Vaishali; Nimbarte, Bhairavi Bhimrao; Bhanare, Rupali Suresh (Journal of Neonatal Surgery, 2025)
Chronobiology has been documented in ancient systems of medicine, including Ayurveda, several millennia ago, albeit in a different language and with different terminology. The ancient texts of Ayurveda highlight the simple living inspired by the rhythms of the natural world, where life and daily activities were designed in sync with the rise of the sun, moon, and the diurnal changes. The core belief Ayurveda is that as much as a person lives in sync with nature's rhythms, that much more health will be maintained. Dinacharya - the daily regimen described in Ayurveda, embodies the principles of chronobiology. The master clock, which is housed in the hypothalamic suprachiasmatic nuclei, regulates the circadian cycle of sleep and wakefulness. In Ayurveda, the fundamental concept of Dosha Kala delineates the dominance of Kapha, Pitta and Vata bioenergies at various times of the day and closely matches the circadian rhythms in hormone release, metabolism, chrononutrition, cognition and a host of other biological processes. Dinacharya practices, including the timing of waking, of meals, of exercise, and sleep, are in harmony with the recent discoveries of chrononutrition and neuroendocrine regulation, clearly indicating that these practices will assist in health promotion, disease prevention, and maintaining a good level of psychophysiological balance. The concept of Aushadha Sevana Kala – the time of administration of the drugs also reflects chronopharmacology, which evidences that action of drugs results from the circadian changes in the absorption and metabolism of drugs. Chronodisruption by not following Dinacharya including late-night eating, sleeping patterns and light exposure, has been associated with chronic conditions like obesity, diabetes and depression. This review presents an integrative exploration of Ayurvedic physiology in relation to modern chronobiology, revisiting the parallels between Ayurvedic ideology and modern science. It encourages further interdisciplinary research to refine and personalise medical practices based on individual rhythms.